2014
DOI: 10.1002/hed.23541
|View full text |Cite
|
Sign up to set email alerts
|

Inflamed benign tumors of the parotid gland: Diagnostic pitfalls from a potentially misleading entity

Abstract: In most cases, a high suspicion index combined with close monitoring of the patient may allow prompt and successful diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…18,19 Consequently, there is a clear potential for a false working hypothesis in preoperative diagnostics in such cases. The aforementioned literature data and our clinical experience show that clinical and imaging approaches can often prove to be demanding in cases of a parotid gland tumor.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Consequently, there is a clear potential for a false working hypothesis in preoperative diagnostics in such cases. The aforementioned literature data and our clinical experience show that clinical and imaging approaches can often prove to be demanding in cases of a parotid gland tumor.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure, allowed an identification rate of the RMV in 98% of the cases which is above that described in literature but is sometimes time consuming. Nevertheless, the variability of the vein and preoperative inflammation and displacement caused by large lesions can be misleading . Lim et al found that the accuracy of the RMV landmark was higher in patients with tumors <2 cm .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the variability of the vein and preoperative inflammation and displacement caused by large lesions can be misleading. 21 Lim et al found that the accuracy of the RMV landmark was higher in patients with tumors <2 cm. 13 Seldom the RMV can run superficially to the FN and lead to misinterpretation of the US findings.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with unclear intraoperative findings, frozen section was performed. There is no doubt that detection of cystadenolymphomas on frozen section is straightforward in the vast majority of cases, and only infarcted or inflamed cases could pose a diagnostic problem . After 17 years of increasing experience in ED, we aimed, in this study, at evaluating the performance and results of minimally invasive surgery in our cases.…”
Section: Discussionmentioning
confidence: 99%